(untitled) (Community Based Medical Journal, 2018)
Soil transmitted helminthes (STHs) infections are common throughout the tropics and subtropics and represents a major public health problem in developing countries. The rate of STHs infection found in the present study was very high in comparison to other countries of this Subcontinent, though they are taking antihelmintics every 6 months interval under Government National Health Program. The present study was carried out to see the Prevalence of STHs infection among the school children in Mymensingh, Bangladesh. A total of 500 stool samples from healthy individuals were collected during April, 2012 to February, 2013 from 20 schools comprising 10 rural and 10 urbans under Sadar upazila, Mymensingh, Bangladesh. The samples were examined in the department of Microbiology, Mymensingh Medical College using saline and iodine preparation microscopy and McMaster technique for the detection of ova of STHs. The STHs prevalence irrespective of the age and sex of the individuals were 37.0% (185) out of 500 specimens where 68.0% (340/500) individuals were male represents the prevalence 38.0% (129/340) and 32.0% (160/500) individuals were female represents the prevalence 35.0% (56/160). Majority of the cases belonged to the age group >5-10 years 50.2% (251/500) of the total, constituted the prevalence 20.2% (101/500) of the total population and 40.2% (101/251) of the individual age group. The distribution of different STHs with their prevalence in the study population where Ascaris lumbricoides (AL) was 63.8% (118), Trichuris trichiura (TT) 37.3% (69), Enterobius vermicularis (EV) 8.1% (15), Ancylostoma duodenale (AD) 7.5% (14), and mixed infection was 15.1% (28). The upper socio-economic class constituted 5.0% (25/500) of the total study population with the prevalence of 20.0% (5/25). The middle socio-economic class constituted 50.0% (250/500) of the total study population with the prevalence of 37.2% (93/250) and the lower socio-economic class constituted 45.0% (225/500) of the total study population with the prevalence of 38.6% (87/225). The urban population constituted 34.0% (170/500) of the total population representing the prevalence 31.2 % (53/170) and rural population constituted 66.0% (330/500) of the total population representing the prevalence 40.0% (132/330). In this study, STHs detection by McMaster method was satisfactory. Thereby, McMaster method could be adapted for rapid detection and quantification of STHs. Moreover, one more frequent administration of antihelmintics with close monitoring of drug administration may reduce the prevalence of STHs infection in Bangladesh. CBMJ 2018 January: Vol. 07 No. 01 P: 04-09